Rancang Bangun Website Company Profil Pusat Pelatihan Pertanian Pedesaan Swadaya Bheger Pemalang - wahyu sulistiyo; Aisyatul Karima; Afandi Nur Aziz Thohari; Eri Eli Lavindi; Fahriah, Sirli (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Information is an important factor in the era of globalization. Service providers in the agricultural sector are not immune from the need for information. In the right way, information can be delivered on target. One way to introduce an agency or community is by processing information and building an information system. The information system can make it easier for the bureaucracy to introduce the Bheger Self-Help Rural Agricultural Training Center or commonly known as